Cation exchanger mixed matrix membrane for copper removal - Rubyatul Jannah, Ismail (2012)
The pollution of heavy metals into environment has attracted a major concern around the world due to their toxicity and adverse effect to the environment.In the current study, cation exchanger mixed matrix membrane (MMM) was produced for the removal of copper in wastewater effluent.Several potential commercial cation resins was screened for maximum copper removal which are Dowex M-31,Dowex MAC-3,Dowex Marathon MSC, Amberlite IR 120,Amberlite IRC 86,Amberlite IRN 150,Lewatit SP 112,Lewatit CNP-105and Lewatit TP 214. The selected resin,Amberlite IR 120 was embedded into ethylene vinyl alcohol (EVAL) polymer and casted into membrane sheet at different cation loading which were 20 and 30 weight %.The effect of copper concentration was studied in batch adsorption experiment.At initial copper concentration of 300 ppm, 20% and 30% cation loading in MMM showed 44.78 and 54.02 mg Cu/g resin binding capacity respectively.The regeneration by using both HCl and H2SO4 give the high percent of copper recovery on MMM with 30% resin loading which were 99.13% and 99.03% respectively.By operating chromatography operation in a membrane format,the limitation of packed bed cation exchanger chromatography such as high-pressure drop,limited flow rate and flow channeling can be overcome.